HUBUNGAN SENAM HAMIL DENGAN KUALITAS TIDUR IBU HAMIL TRIMESTER III DI DESA PECALUNGAN KECAMATAN PECALUNGAN KABUPATEN BATANG: Relationship Between Pregnancy Exercise With Sleep Quality Of Pregnant Women In Trimester Iii In Pecalungan Village, Pecalungan District, Batang Regency - Agustina Riftianggi (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2022)
Pregnancy enters the third trimester, there are physical and psychological changes. This condition causes pregnant women to experience complex complaints such as discomfort that affects sleep quality. One solution to overcome this discomfort is pregnancy exercise. Based on the preliminary study, data obtained from 10 pregnant women, 3 pregnant women with poor sleep quality, and 7 pregnant women with good sleep quality. The purpose of this study was to determine the relationship between pregnancy exercise and sleep quality of third trimester pregnant women in Pecalungan Village, Pecalungan District, Batang Regency. This type of research is an analytical survey. The research method used is cross-sectional. The population in this study were 36 pregnant women. The research sample was 36 pregnant women taken by total sampling. Collecting data in this study using a questionnaire by distributing questionnaires to respondents with a number of written questions used to obtain information from respondents, using the Chi Square correlation test. The results showed that there was a relationship between pregnancy exercise and the quality of sleep of pregnant women with p-value = 0.000 <0.05. The conclusion of this study is that there is a relationship between pregnancy exercise and sleep quality of pregnant women in Pecalungan Village, Pecalungan District, Batang Regency